Energy transfers and reflexion of infragravity waves at a dissipative beach under storm waves. - Bertin, Xavier (Zenodo, 2020)
%%% Author: Xavier Bertin (xbertin@univ-lr.fr) %%% %%% Date: 15/04/2020 %%% %%% Purpose: This repository provides the field observations and XBeach model input %%% %%% required to reproduce the results presented in paper referred below. %%% %%% Reference: Bertin, X., Martins, K., de Bakker, A., Guérin, T., Chataigner, T., %%% %%% Coulombier, T. et de Viron, O., 2020. Energy transfers and reflexion of %%% %%% infragravity waves at a dissipative beach under storm waves. In press %%% %%% to Journal of Geophysical Research-Ocean. %%% %%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%% *The directory Obs includes: -The wave bulk parameters computed as explained in the paper for the 10 sensores used in this study: the offshore ADCP1, the intertidal PT1, PT2, ADCP2/PT3, PT4, PT5, ADV/PT6, PT7/Altus, PT8 and PT9. Each file has the same format and includes: the date (YYYY MM DD), the time (HH MM SS), the mean water depth, the spectral significant wave height Hm0, mean wave periods Tm01 and Tm02, the discrete and continuous peak periods, the energetic wave period Tm0,-2 and the spectral significant height of IG waves Hm0,IG. -The spectral significant height Hm0,IG+ and mean wave period Tm02,IG+ of incoming IG waves separated at the ADCP2 and ADV using the method of Guza et al. (1984). The two files have the same format and includes the date (YYYY MM DD), the time (HH MM SS), Hm0,IG+ and Tm02,IG+. -The position of each sensore measured with a geodetic GNSS and provided in the same datum as the bathymetry used in the model (Lambert93 and mean sea level). *The directory XBeach includes all the necessary files required to reproduce the simulations presented in this study -The bathymetry interpolated over a rectilinear grid, with X and Y given in Lambert93 coordinates (files X_L93.grd and Y_L93.grd) and Z referred with respect to mean sea level (Z_L93.grd). -The water level fluctuations measured at ADCP1 (WLevel_ADCP_201702.dat). -The XBeach input file (params.txt) and a file providing the list of directional wave spectra provided in the directory "Spectra_WWIII". These spectra were computed from a regional application of WaveWatchIII over the North Atlantic Ocean and forced with CFSR wind fields but they were converted in the format of SWAN, readable by XBeach. : {"references": ["Bertin, X., Martins, K., de Bakker, A., Gu\u00e9rin, T., Chataigner, T.,\u00a0Coulombier, T. et de Viron, O., 2020. Energy transfers and reflexion of infragravity waves at a dissipative beach under storm waves. In press\u00a0\u00a0to Journal of Geophysical Research-Ocean"]}